2020
DOI: 10.3389/fphar.2020.01141
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials for Autophagy-Related miRNA-34a Delivery in Cancer Treatment

Abstract: Autophagy is an evolutionary conserved physiological process with a fundamental role during development, differentiation, and survival of eukaryotic cells. On the other hand, autophagy dysregulation is observed in many pathological conditions, including cancer. In particular, tumor growth and progression are accompanied and promoted by increased autophagy that allows cancer cells to escape apoptosis and to proliferate also in harsh microenvironments. It is, therefore, clear that the impairment of the autophagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 148 publications
0
11
0
Order By: Relevance
“…Autophagy is a process of engul ng one's own cytoplasmic proteins or organelles, coating them into vesicles, and then fusing with lysosomes to degrade the contents of the package. A large number of studies had con rmed that miRNA can regulate autophagy [22,23]. Abnormal autophagy function leads to the accumulation of apoptosis and induces the production of autoantibodies, thereby inducing and aggravating the condition of SLE.EIF4EBP1 can regulate mTORC1 to induce autophagy [24], microtubulassociated protein 1 light chain 3 (LC3) is a key protein involved in autophagy [25].…”
Section: Disease Progression Of Mrl/lpr Lupus Mice After Experimental Intervention Of Mir-99a-3p In Vivomentioning
confidence: 99%
“…Autophagy is a process of engul ng one's own cytoplasmic proteins or organelles, coating them into vesicles, and then fusing with lysosomes to degrade the contents of the package. A large number of studies had con rmed that miRNA can regulate autophagy [22,23]. Abnormal autophagy function leads to the accumulation of apoptosis and induces the production of autoantibodies, thereby inducing and aggravating the condition of SLE.EIF4EBP1 can regulate mTORC1 to induce autophagy [24], microtubulassociated protein 1 light chain 3 (LC3) is a key protein involved in autophagy [25].…”
Section: Disease Progression Of Mrl/lpr Lupus Mice After Experimental Intervention Of Mir-99a-3p In Vivomentioning
confidence: 99%
“…Many studies have confirmed that miRNAs regulate autophagy 21,22 . Abnormal autophagy leads to the accumulation of apoptotic cells and induces the production of autoantibodies.…”
Section: Discussionmentioning
confidence: 99%
“…The roles of autophagy are dynamic in different stages of tumorigenesis and development, with a possible inhibitor of occurrence of tumors at the early stage but an underlying pro-tumoral factor for invasion and metastasis at the late stage ( 23 ). Although certain autophagy-related mRNAs and miRNAs have been verified to predict the survival of ccRCC patients and a large number of risk score models based on differentially expressed ARGs and autophagy-related miRNAs have been established to forecast survival ( 24 , 25 ), most reports indicated these ARGs, absence in the missions of encoding proteins; therefore, lncRNAs gain more specificity on evaluating tumor actual conditions than other types of biomarkers. Given the inherent advantages of lncRNAs on cancer biological processes and the remarkable autophagy correlation of ARLNRs, exploring their values on predicting the prognosis of patients with ccRCC is eagerly awaited.…”
Section: Discussionmentioning
confidence: 99%